Co-Solvent Free Electrochemical Synthesis of Biodiesel Using Graphite Electrode and Waste Concrete Heterogeneous Catalyst: Optimization of Biodiesel Yield - Wiyogo Prio Wicaksono; Sekar Asmara Jati; Ika Yanti; Prastika Krisma Jiwanti (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
This study optimized a co-solvent free electrochemical method for biodiesel synthesis using graphite electrode and waste concrete heterogeneous catalyst. Various parameters were evaluated, including: applied voltage (9.6, 14.4, 19.2 V), catalyst particle size uniformity (unfiltered and filtered with 150 mesh), and reaction time (15, 30, 120, 240 min). The results obtained 100% FAME content and 78.51% of biodiesel yield that were achieved at 14.4 V within 30 min using filtered catalyst and cooking oil feedstock. However, a slight decline was observed with the use of waste cooking oil. This optimized method offers a reliable and simple condition for mass biodiesel production. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).